MK-8325: A silyl proline-containing NS5A inhibitor with pan-genotype activity for treatment of HCV. Issue 10 (1st June 2018) - Nair, Anilkumar G.; Zeng, Qingbei; Selyutin, Oleg; Rosenblum, Stuart B.; Jiang, Yueheng; Yang, De-Yi; Keertikar, Kerry; Zhou, Guowei; Dwyer, Michael; Kim, Seong Heon; Shankar, Bandarpalle; Yu, Wensheng; et al.
Graphical abstract: HCV NS5A inhibitors have shown impressive in vitro potency profiles in HCV replicon assays thus making them attractive components for inclusion in an all oral fixed dose combination regimen. Herein, we describe the discovery and characterization of silyl proline-containing HCV NS5A inhibitor MK-8325 with pan-genotype activity and acceptable pharmacokinetic properties. Abstract: HCV NS5A inhibitors have shown impressive in vitro potency profiles in HCV replicon assays thus making them attractive components for inclusion in an all oral fixed dose combination regimen. Herein, we describe the discovery and characterization of silyl proline-containing HCV NS5A inhibitor MK-8325 with good pan-genotype activity and acceptable pharmacokinetic properties.